2017
DOI: 10.1080/13880209.2017.1302484
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effect of Stachys pilifera ethanol extract in carbon tetrachloride-induce hepatotoxicity in rats

Abstract: Context:Stachys pilifera Benth (Lamiaceae) has long been used to treat infectious diseases, respiratory and rheumatoid disorders in Iranian folk medicine. Antitumor and antioxidant activity of the plant have been reported.Objective: The study was designed to assess the hepatoprotective activity of ethanol extract of Stachys pilifera in carbon tetrachloride (CCl4)-induced hepatotoxicity in rats.Materials and methods: The rats were randomly divided into six equal groups (n = 7). Group I was treated with normal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 24 publications
6
18
0
1
Order By: Relevance
“…The results indicated that treatment with SL400 mg/kg diminished renal oxidative injury in the GM group (group II) by improving the status of the abovementioned antioxidants. These findings are consistent with the antioxidant effects of ethanol extract from Stachys pilifera in reducing elevated hepatic MDA levels of a CCl4induced liver injury in a rat model (Panahi Kokhdan et al 2017).…”
Section: Groupssupporting
confidence: 88%
“…The results indicated that treatment with SL400 mg/kg diminished renal oxidative injury in the GM group (group II) by improving the status of the abovementioned antioxidants. These findings are consistent with the antioxidant effects of ethanol extract from Stachys pilifera in reducing elevated hepatic MDA levels of a CCl4induced liver injury in a rat model (Panahi Kokhdan et al 2017).…”
Section: Groupssupporting
confidence: 88%
“…However, hydroalcoholic extract of S.P.B. resolved in distilled water, orally treated to rats at the dose of 500 mg/kg (Panahi Kokhdan et al, 2017). Group 1 as a control, intraperitoneally pretreated with a dose of normal saline before treatment with distilled water for 12 days.…”
Section: Methodsmentioning
confidence: 99%
“…The oil of this plant is mainly consisted of cis ‐chrysanthenyl acetate, cis ‐chrysanthenol, spathulenol, β‐caryophyllene, linalool, and terpinen‐4‐ol (Javidnia, Miri, Moein, Kamalinejad, & Sarkarzadeh, 2006). Moreover, phytochemical studies have shown the presence of compounds such as diterpenes, phenylethanoid glycosides, saponins, terpenoides, and flavonoids in Stachys species (Panahi Kokhdan et al, 2017). The aerial parts of S.P.B.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been revealed that the hydroalcoholic extract of S. pilifera is an effective natural substance to suppress inflammation in various animal models. Sadeghi et al ., identified the hepatoprotective effect of S. pilifera Benth on CCl 4 -induced hepatotoxicity in rats( 14 ).…”
Section: Introductionmentioning
confidence: 99%